DISTRIBUSI PENDAPATAN PETANI LAHAN KERING DI KECAMATAN PARANGGUPITO KABUPATEN WONOGIRI - Setyowati, Setyowati (Universitas Sebelas Maret, 2004)
This study aimed to knowing the income and it distribution of the land arid farmer at Paranggupito Subdistrict in Wonogiri Regency. The thought scheme of this study that is: income farmer is determinant by three factors, there is: productivity, value market of the productivity and cost of production. To knowing balance or not of their income is accepted, it used income distribution analysis. This study use descriptive method. And the application technique is used by survey technique with questioner. Sample technique is done by choosing the sub district intentionally and by consideration of the poor sub district, and there are arid/dry land. So that to choose the Paranggupito sub district as a sample. And from this sub district to take 30 family of the farmer as sample. The obtained data is analyzed by income distribution analysis, that is to use Gini Index (GI). From this study was knowed that : big income was obtained by the farmer from agricultural arid land at sub district Paranggupito Wonogiri regency is Rp. 1.595.947 per years or Rp. 132.995 per months. The income like that is considered that very low and can not becoming hope to fulfill the farmer family necessity. This assumption is confirmed by the facts that income distribution analysis with Gini Index approach shows that Gini Index value is 0,89 include to heavy unstable criteria and ii shows income distribution land arid farmer at Paranggupito sub district Wonogiri regency is not unequal.